Formulation of a magnetic-pickering emulsion - Chua, Keith Boon Meng (2018)
Emulsions are colloidal suspensions of both oil and water phases where one is dispersed in the other. Instead of using surfactants, Pickering emulsions use colloidal nanoparticles. In magnetic Pickering emulsions, magnetic particles are used for the stabilization as they are easier to manoeuvre and control. Ferritin is an example of a magnetic particle. It is a protein nano-cage with an empty core. This core can store iron which makes it magnetizable. It has a diameter of 12 nm and is used to regulate blood iron levels in the human body. It can adsorb at the oil-water interface and encapsulate dispersed droplets. This results in the stabilization of emulsions. To use ferritin for formulating magnetic Pickering emulsions, iron must be loaded onto it first. After iron is loaded onto the ferritin, it will be conjugated with a fluorescent dye to allow it to be observed easily. The ferritin will then be used with rosemary oil to form an emulsion. This emulsion will undergo optical and confocal microscopy which will allow us to observe its structure and its stability. The response of ferritin to a magnet will also be tested and observed under an optical microscope.